PENGEMBANGAN MEDIA KARIER BERBASIS INSTAGRAM TERHADAP PILIHAN KARIER SISWA SMP TINGKAT IX - Inggriana, Ririn Nuri; Fatimah, Siti; Irmayanti, Rima (IKIP Siliwangi, 2024)
One of the services of Counseling Guidance is in the career field. The purpose of this study is to develop an Instagram-based career media for the career choices of junior high school students at level IX. . The subjects in this study were 35 grade IX students and 3 validator experts to test the feasibility of Instagram media. This study uses the R&D (Research and Development) method which is limited to 7 stages. The data analysis used is a feasibility test to determine the feasibility of Instagram to be used for students' career choices and a t-test used to determine the effectiveness of Instagram on students' career choices. Based on the results of the product feasibility test expert, it was stated that Instagram was in the